Bacterial flora of liver abscesses from feedlot cattle fed with or without tylosin - A.B. Beharka; L.H. Carroll; A.P. Raun; S.B. Laudert; J.C. Parrott; Tiruvoor G. Nagaraja; M. M. Chengappa (Kansas Agricultural Experiment Station Research Reports, 1996)
Fusobacterium necrophorum was the predominant bacterial isolate from liver abscesses of feedlot cattle fed with or without tylosin. The major difference in the bacterial flora of liver abscesses between cattle groups was the higher incidence of Actinomyces pyogenes in the tylosin-fed cattle. Because the minimum inhibitory concentration of tylosin was not different between bacterial isolates from cattle in the two treatments, we concluded that continuous feeding of tylosin does not induce resistance. The source of A. pyogenes infection and significance of A. pyogenes interaction with F. necrophorum in tylosin-fed cattle are not known.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Liver abscesses; Fusobacterium necrophorum; Actinomyces pyogenes; Tylosin